(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Every employee’s individual performance influences the entire team or even the firm. It also clarifies the employee’s role and status in the organization. Performance appraisal allows you to provide either positive or negative feedback as well as identify areas for improvement. If the appraisal of the job employees is lower than their expectation, they will reduce attendance with lower performance and even quit the job, which is the last thing that the managers expect. Assessment of Performance Appraisal given on Employee in terms of Evaluative: The first statement has a weighted mean of 3.48, which is the highest, while the fourth statement has a weighted mean of 3.32, which is the lowest. Cognitive: The first statement has a weighted mean of 3.50, which is the highest, while the fourth statement has a weighted mean of 3.36, which is the lowest. Behavioral: The first statement has a weighted mean of 3.50, which is the highest, while the fourth statement has a weighted mean of 3.18, which is the lowest. Factors that affect Employee Productivity in terms of Skills Acquisition: The first statement has a weighted mean of 3.62, which is the highest, while the fourth statement has a weighted mean of 3.34, which is the lowest. Motivation: The first statement has a weighted mean of 3.62, which is the highest, while the fourth statement has a weighted mean of 3.36, which is the lowest. Leadership: The first statement has a weighted mean of 3.58, which is the highest, while the fourth statement has a weighted mean of 3.52, which is the lowest. It is a must to provide more learning opportunities to their employees. Improving performance and productivity are not the only things that can benefit employee learning, and making knowledge out of it is also part of the opportunities that employees can get if provided. At this time, not all employees can get knowledge without having someone help them get it; on the contrary, to get that kind of opportunity, the employee must have the qualifications to do so.